Honeybee products as potential bioindicators of heavy metals contamination from Northern Vietnam - Ngat, Tran Thi; Xuan Lam, Truong; Gia Minh, Hoang; Thi Phuong Lien, Nguyen (Vietnam Journal of Biotechnology, 2020)
Contamination of heavy metals (As, Cd, Hg, Pb and Sn) in honeybee products (Apis cerana) from Northern Vietnam is determined. The study was carried out in two main harvesting seasons of beekeeper farms (April and October), over two years (2018-2019). A total of 72 samples from 24 honeybee hives from 8 provinces and one city were collected. The results showed that the quality of three products in nearly all research sites were met the standards in accordance with the national technical regulation on the limits of heavy metal contamination in food of the Vietnamese Health Ministry, except for the pollen and beeswax from HY2 site. The concentration of Pb was most notably value in this study, which was determined at fairly high levels in pollen (3,767 mg/kg) and beeswax (5,840 mg/kg) from HY2 site. This can be a warning for this metal significant contamination in the habitat. Specially, Hg was not detected in most samples or only recorded without significant. For the environmental types, the mean value of As and Sn in all honeybee’s product types in semi-rural area were higher than that in rural area. Thus, the detection of the heavy metals proves that honeybee’s products could be good indicators to detect the environmental contaminants and monitor the habitat quality of a particular area